2010
DOI: 10.1021/jp101003g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on AuPd Nanoparticles Produced by Inert Gas Condensation

Abstract: Bimetallic nanoparticles of AuPd were synthesized using the inert gas condensation technique, where the material is sputtered from a target and the particles are formed in an inert condensation zone. Throughout the synthesis process and jointly with the control of the atmosphere conditions, the region after the condensation chamber was kept at a fixed temperature, and several experimental runs were performed at 700 and 1000°C. The synthesis conditions were set to produce particles of 5 nm of diameter, and almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In physical methods of Pd-alloy NP synthesis, sequential or coevaporation of the two components using e-beam, thermal heating, sputtering, and laser ablation has been employed for growing Pd alloy thin films, nanocrystalline, and nanoparticulate layers. [7][8][9][10] These techniques normally yield alloy thin films or nanoparticulate layers of undefined topography, having large variations in composition or metallic and alloy multiphases in the same sample. In chemical methods, electrochemical synthesis, chemical reduction, and thermal decomposition of Pd or Pd-alloy complexes are widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In physical methods of Pd-alloy NP synthesis, sequential or coevaporation of the two components using e-beam, thermal heating, sputtering, and laser ablation has been employed for growing Pd alloy thin films, nanocrystalline, and nanoparticulate layers. [7][8][9][10] These techniques normally yield alloy thin films or nanoparticulate layers of undefined topography, having large variations in composition or metallic and alloy multiphases in the same sample. In chemical methods, electrochemical synthesis, chemical reduction, and thermal decomposition of Pd or Pd-alloy complexes are widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of those methods is presented in Figure 4. Although examples of the usage of nanoclusters synthesized using different methods for gas sensing applications will be presented in this review, special focus will be given to nanocluster synthesis using the inert gas condensation technique because of its many advantages as discussed below [42][43][44][45].…”
Section: Nanocluster Device Fabricationmentioning
confidence: 99%
“…The icosahedral shape was selected due to its common appearance on silver (and other metal) particles at this range of sizes (Perez-Tijerina et al 2010), and because with this choice, a small number of nonequivalent orientations can be used to form the set of starting configurations. Ten different orientations were considered in this study: (i) edge-to-edge, (ii) edge-to-face, (iii) edge-to-vertex, (iv) edge-to-random, (v)face-to-face, (vi) face-to-vertex, (vii) face-torandom, (viii) vertex-to-vertex , (ix) vertex-to-random, and (x) random-to-random.…”
Section: The Collision Modelmentioning
confidence: 99%
“…Different velocities were tested for each orientation, ranging from 0 m/s (pure coalescence at contact) to 500 m/s; this range of velocities covers the typical conditions at which the particles collide in an inert gas condensation process (Perez-Tijerina et al 2010). It was found that in this range only the velocity of 500 m/s gave the particles the enough kinetic energy to deform the original nanoparticles to promote the creation of a new nanoparticle, with a well-defined center.…”
Section: The Collision Modelmentioning
confidence: 99%